The Analysis of The Project-Based Learning Model Used by The English Teacher of Junior High School Kabupaten Jeneponto - Ramlah Ramlah; Syamsiarna Nappu; Asriati AM (Institut Agama Islam Negeri Palopo, 2023)
The research aimed to investigate how teachers implemented the Project-Based Learning Model in teaching English, as well as the challenges faced by an English teacher at SMPN 2 Turatea. The researcher employed a Qualitative Research Design Method and collected data through two instruments: lesson plans, teacher recordings, and interview guides. The gathered data underwent analysis involving data reduction, data display, and conclusion drawing. The Project-Based Learning Model consists of six stages: initiating with an essential question, designing a project plan, creating a schedule, monitoring student progress and project advancement, assessing outcomes, and evaluating the overall experience.The findings revealed that the teacher followed all six stages of the Project-Based Learning Model in teaching English. These stages encompassed starting with an essential question, crafting a project plan, establishing a timeline, closely monitoring student progress and project development, evaluating outcomes, and reflecting on the learning experience. Notably, the teacher innovatively employed control cards to oversee students' project progress. The teacher perceived that integrating the Project-Based Learning Model into English instruction not only promoted the development of positive character traits, particularly self-confidence but also encouraged student engagement in meaningful interactions.